Clinical evaluation of total intravenous anaesthesia using xylazine or dexmedetomidine with propofol in surgical management of canine patients - Biswadeep Jena; Jayakrushna Das; Indramani Nath; Kautuk Kumar Sardar; Abhishek Sahoo; Sasanka Sekhar Beura; Abhishek Painuli (Veterinary World, 2014)
Aim: The aim was to evaluate and compare the clinico-physiological, hemodynamic and hematobiochemical effects in response to different total intravenous anaesthesia techniques using xylazine or dexmedetomidine with propofol in canine patients. Materials and Methods: Under a prospective randomized blinded clinical study, 12 apparently healthy adult dogs (14.27±3.2 kg) divided into two groups (n=6). Animals were administered with xylazine (0.5 mg/kg body weight IV) in X group or, dexmedetomidine (10 μg/kg body weight IV) in D group and propofol (as IV bolus till the induction and continuous IV infusion for maintenance). Clinical reflexes, physiological, hemodynamic parameters, were recorded at 5-min intervals. Blood was collected at zero, 30 and 60 min after initial injection for hematobiochemical evaluation. Statistical analysis was performed using analysis of variance, Duncan’s multiple range tests, paired - t-test and Kruskal–Wallis one-way test. Results: Animals showed quicker attenuation of all clinical reflexes in group D. Induction doses of propofol were 3.17±0.21 and 2.72±0.15 mg/kg and rate of infusion of propofol for maintenance of anaesthesia were 0.33±0.02 mg/kg/min and 0.35±0.02 mg/kg/min respectively in group X and D. Recovery was quicker in group D. There were no significant statistical differences in physiological, hemodynamic and hematobiochemical parameters in both the groups. There were no adverse effects after recovery. Conclusion: Both anesthetic protocols provided satisfactory immobilization, but dexmedetomidine-propofol combination may be preferred owing to slightly better degree of basal anaesthesia, lesser doses of propofol required for induction and maintenance of anaesthesia along with a lesser degree of respiratory depression. However, there was no clear preference for either of the protocol, and both appear suitable for canines.